1) x + 8 = 11
2) x = 3
3) x - 2y = 11 --> x = 2y + 11
4) -7(2y + 11) - 2y = -13
5) -14y - 77 - 2y = -13
6) -16y - 77 = -13
7) -16y = 64
8) y = -4
9) x - 2(-4) = 11
10) (3, -4)
Put the steps in order that are used to solve the following systems of equations by substitution.
-7x-2y= -13
x-2y = 11
-16y = 64
= x-2y = 11 --> x = 2y + 11
-14y - 77 - 2y = - 13
-7(2y + 11) - 2y = - 13
(3, -4)
-16у - 77 = -13
x + 8 = 11
y = -4
x = 3
x - 2 (-4) = 11
Put the steps above in the right order, only use the numbers I listed above
1 answer